Reduction of energy consumption by AC due to air tightness and ventilation strategy in residences in hot and humid climates - Uno, Tomoko; Hokoi, Shuichi; N. Ekasiwi, Sri Nastiti; Abdul Majid, Noor Hanita (Architectural Institute of Japan, 2012)
This paper proposes strategies for reducing energy consumption for cooling in residences in hot and humid climates.Based on the results of fieldwork measurements and questionnaire surveys, a simulation of indoor thermal environments in consideration of AC operation was carried out, in order to evaluate energy consumption by AC.This simulation program takes into account both heat and moisture conductivity in building materials.The combined effects of building air-tightness and the opening time of doors and windows for ventilation were examined.Making the entire building airtight results in a small reduction in energy consumption, since the air-conditioned area increases.Irrespective of this, night-time ventilation of non-air-conditioned spaces is quite effective in reducing sensible cooling load.Since energy consumption for cooling is expected to increase rapidly in hot and humid areas along with economic growth and improvement of indoor environment quality, introduction of not only a high degree of insulation but also air-tightness along with well controlled ventilation is required to achieve energy savings.